Adherence to the American Diabetes Association retinal screening guidelines for population with diabetes in the United States. (4th May 2018) - An, JaeJin; Niu, Fang; Turpcu, Adam; Rajput, Yamina; Cheetham, T Craig
ABSTRACT: Purpose : (1) To assess long-term adherence to American Diabetes Association guideline-recommended retinal screening among population with diabetes in the United States. (2) To determine factors associated with long-term adherence to routine eye screening exams. Methods : A retrospective cohort study was conducted in adult patients with diabetes identified from January 2009 to December 2010. Patients were followed until disenrollment, death, or study end date (December 2013). A patient was defined as adherent when having at least one exam in each 12-month period if there was evidence of retinopathy, or at least one exam in each 24-month period if there was no evidence of retinopathy. Multivariate logistic regressions were used to investigate patient demographics and other baseline characteristics associated with adherence to guidelines. Results : A total of 204, 073 patients were identified; the mean age (SD) was 61 (13) years and 48% were female. Overall, 71.1% were adherent to the retinal screening guidelines during a median of 4.8 years of follow-up including 27.7% who received an eye exam every year. Patient socioeconomic status (younger age, black race, lower income/education), less comorbidity, insulin use, higher specialist copayment plans, and proxies for poor patient behavior (lower adherence to the oral hypoglycemic agents, less diabetes education, hemoglobin A1C >9%) were associated with nonadherence to routine eye screening exams. Conclusion : During nearly 5 years of follow-up, 28.9% of patients with diabetes were nonadherent to the retinal screening guidelines. Future research should focus on the development of interventions to address modifiable factors associated with nonadherence.